Planning and Restoration of Environmental Values in Nigeria Dysfunctional Societies - Basorun, J. O; Ayeni, D.A (European Journal of Sustainable Development, 2013)
Urban centers in Nigeria are becoming dysfunctional – a situation that threatens ourenvironmental values. This study, examines the pattern, process and problems of thesesocieties which experience rapid urban development pressure on account of highpopulation growth and decentralization of governance in the form of states and localgovernment creations. The study adopts extensive review of literature and findings revealthat Nigeria records very high level of urbanization and pollution, lacks effective culturaland physical planning policies, mismanages its urban open spaces, without adequatepersonnel to plan and organize the urban environments. Recommendations were madeon ways of restoring these environmental values through effective planning of urbancenters in Nigeria.